2006
DOI: 10.1029/2005jb004253
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the North American plate interior from a decade of continuous GPS measurements

Abstract: A combination of two independent geodetic solutions using data from close to 300 continuous GPS stations covering the central and eastern United States shows that surface deformation in the North American plate interior is best fit by a model that includes rigid rotation of North America with respect to ITRF2000 and a component of strain qualitatively consistent with that expected from glacial isostatic adjustment (GIA). After correcting for the North American plate motion, residual horizontal velocities show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
148
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 55 publications
(99 reference statements)
21
148
0
2
Order By: Relevance
“…From literature on geodetic solutions, we selected purely GPS solutions only. The pole and rate of Calais et al [2006c] are estimated from several hundred stations to the south of the Hudson Bay, chosen far from the center of the glacial isostatic adjustment (GIA) over the Hudson Bay. All other solutions are based on a much smaller set of stations not necessarily far from the GIA center.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…From literature on geodetic solutions, we selected purely GPS solutions only. The pole and rate of Calais et al [2006c] are estimated from several hundred stations to the south of the Hudson Bay, chosen far from the center of the glacial isostatic adjustment (GIA) over the Hudson Bay. All other solutions are based on a much smaller set of stations not necessarily far from the GIA center.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…For example, GPS measurements suggest that horizontal deformation across North America east of the Rocky Mountains amounts to $ 1 mm yr À1 ( 1 nanostrain yr À1 ), which is dominated by subtle deformation associated with Holocene glacial isostatic rebound [Calais et al, 2006;Sella et al, 2007]. Geodetic evidence for localized accelerated deformation in the epicentral region of three 1811 -1812 M > 7 New Madrid earthquakes continues to be debated [Calais et al, 2006;Smalley et al, 2005]. Estimates of intraplate strain across India from early campaign-mode GPS data [Paul et al, 2001] and historic seismic moment release [Bird and Liu, 2000;Rao, 2000] suggest deformation at 2 -7 nanostrain yr À1 (northsouth shortening) and 0.2-0.6 nanostrain yr À1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Velocities with magnitudes exceeding 1 mm/yr occur near the Great Lakes as well as to the north and east of the Great Lakes. Both Calais et al [7] and Sella et al [25] had previously identified such motion occurring near and adjacent to the Great Lakes, and they attributed this horizontal motion to glacial isostatic adjustment associated with the melting of Laurentide ice masses, which occurred more than 10,000 years ago. Horizontal velocities in this area are generally less than 2 mm/yr in magnitude and exhibit flow directed outward from Hudson Bay where the Laurentide ice mass is thought to have been thickest during the Last Glacial Maximum.…”
Section: Velocities Relative To Stable North Americamentioning
confidence: 99%